2019
DOI: 10.3389/fevo.2019.00448
|View full text |Cite
|
Sign up to set email alerts
|

Turn-Taking Between Provisioning Parents: Partitioning Alternation

Abstract: How parents negotiate over parental care is a central issue in evolutionary biology because it affects the evolutionary outcome of sexual conflict. A recent theoretical model shows that "turn-taking" in provisioning visits by the parents can be an evolutionarily stable negotiation strategy, and empirical studies have shown that parental nest-visits do indeed alternate more than expected by chance. However, such alternation may also be generated by a refractory period, or by correlated temporal heterogeneity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Empirical studies in songbirds have indicated that individuals modify their provisioning rate in response to the partner's experimentally manipulated behaviour, for example, selective playback, handicapping manipulations (reviewed in Harrison et al, 2009). More recently, it has also been argued that parents alternate their visits at the nest more than expected by chance because they actively monitor and respond to each visit of the partner (Johnstone et al, 2014; Savage et al, 2017; but see Schlicht et al (2016) and Baldan, Hinde, et al (2019). Therefore, parents are behaviourally responsive to each other, but it is not currently known which behavioural mechanisms are underlying these responses.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies in songbirds have indicated that individuals modify their provisioning rate in response to the partner's experimentally manipulated behaviour, for example, selective playback, handicapping manipulations (reviewed in Harrison et al, 2009). More recently, it has also been argued that parents alternate their visits at the nest more than expected by chance because they actively monitor and respond to each visit of the partner (Johnstone et al, 2014; Savage et al, 2017; but see Schlicht et al (2016) and Baldan, Hinde, et al (2019). Therefore, parents are behaviourally responsive to each other, but it is not currently known which behavioural mechanisms are underlying these responses.…”
Section: Introductionmentioning
confidence: 99%
“…Four non-mutually exclusive scenarios are possible. First, spatial heterogeneity (habitat fragmentation), lower food availability or human disturbance in the urban environment may decrease coordinated behaviours because parents may need to forage in different locations 24 or further away from the nest 57 . Empirical evidence in zebra finches Taeniopygia guttata showed that parents foraging independently from each other at different foraging areas decreased synchrony of nest visits 16 .…”
Section: Discussionmentioning
confidence: 99%
“…parental workload 16 , 21 , 22 , offspring need during development 23 ) affecting pair coordination, a remaining gap in knowledge is how environmental and ecological conditions might limit the ability of parents to coordinate care 24 , 25 . In particular, a study on a great tit ( Parus major ) population in a deciduous forest has shown that pairs in close proximity and recorded on the same day have similar levels of coordination, possibly due to a shared environment (e.g., local weather condition, resource availability) 24 . Therefore, studying the environmental effects on pair coordination is central to understand possible ecological constraints to the emergence of parental behaviours and their fitness consequences.…”
Section: Introductionmentioning
confidence: 99%
“…2017); (but see Schlicht et al . (2016) and Baldan, Hinde and Lessells (2019)). Therefore, parents are behaviourally responsive to each other, but it is not currently known which behavioural mechanisms are underlying these responses.…”
Section: Introductionmentioning
confidence: 98%